Hubungan Antarpribadi dalam Film Pendek “Tak Lagi Sama”: Perspektif Sosiologi Komunikasi - Nanda Syukerti; Lovia Evanne; Ani Sagita (Komsospol, 2021)
In forming individuals, interpersonal relationships have an important role, through interpersonal relationships are expected to be able to encourage someone to have feelings, understanding, and support and help individuals to understand the expectations of other individuals. There are several theories to reduce this phenomenon, which specifically generalizes the concept of interpersonal relationships which have an important role in shaping individuals, through interpersonal relationships are expected to be able to encourage someone to have a feeling, understanding and support and help individuals to understand the expectations of others. Another individual In the film "No Longer the Same" starring Salshabilla Andriani and Yusuf Mahardika, there are several scenes depicting the interpersonal relationships between the characters in the film, this film was released on June 18, 2021 on Salshabilla Andriani's Youtube channel. The purpose of the study was to find out how the interpersonal relationships in the film "No Longer the Same". This type of research is descriptive qualitative, analyzing the interaction of interpersonal relationships in the short film "Tak Lagi Sama". So the theory that can be used in this research is interpersonal relationship. The results of this study are the interpersonal relationships that occur in the film are relationship development, relationship maintenance and relationship termination, there are also self-disclosure, process view and social exchange.